Next-Generation Sequencing Reveals a Novel Emaravirus in Diseased Maple Trees From a German Urban Forest - Rumbou, Artemis; Candresse, Thierry; von Bargen, Susanne; Büttner, Carmen (Frontiers in Microbiology, 2021)
While the focus of plant virology has been mainly on horticultural and field crops as well as fruit trees, little information is available on viruses that infect forest trees. Utilization of next-generation sequencing (NGS) methodologies has revealed a significant number of viruses in forest trees and urban parks. In the present study, the full-length genome of a novel Emaravirus has been identified and characterized from sycamore maple (Acer pseudoplatanus) - a tree species of significant importance in urban and forest areas - showing leaf mottle symptoms. RNA-Seq was performed on the Illumina HiSeq2500system using RNA preparations from a symptomatic and a symptomless maple tree. The sequence assembly and analysis revealed the presence of six genomic RNA segments in the symptomatic sample (RNA1: 7,074 nt-long encoding the viral replicase; RNA2: 2,289 nt-long encoding the glycoprotein precursor; RNA3: 1,525 nt-long encoding the nucleocapsid protein; RNA4: 1,533 nt-long encoding the putative movement protein; RNA5: 1,825 nt-long encoding a hypothetical protein P5; RNA6: 1,179 nt-long encoding a hypothetical protein P6). Two independent NGS sequencing runs from the same symptomatic maple tree detected the same genome segments. For one of these sequencing runs the cDNA library was prepared using a primer targeting the conserved genome terminal region, known to be shared between emaraviruses genome segments. We suggest, therefore, that the six identified genome segments represent the complete genome of a novel emaravirus from maple, which we tentatively name maple mottle-associated virus (MaMaV). Phylogenetic and sequence homology analyses place this virus on the distinct “subgroup a” clade within the Emaravirus genus along with - among others - rose rosette emaravirus, actinidia emaravirus 2, and fig mosaic virus. Validation RT-PCR assays performed on symptomatic and non-symptomatic trees suggest that MaMaV may be the symptom-inducing virus in the diseased trees. To our knowledge, this is the first time an Emaravirus is described from maple and is fully genetically characterized. With the discovery of MaMaV, the genus Emaravirus comprising negative-sense single-stranded viruses with very divergent genomes - that were until recently overlooked - has substantially increased counting 22 established and putative members.